Efficacy of trapping systems for monitoring of Afrotropical fruit flies. (24th January 2017) - Manrakhan, A.; Daneel, J.‐H.; Beck, R.; Virgilio, M.; Meganck, K.; De Meyer, M.
Abstract: The efficacy of different attractant trap combinations for monitoring of Afrotropical fruit flies was evaluated in commercial fruit production areas and natural areas in the northern parts of South Africa. Five food‐based attractants: three‐component Biolure, a combination of ammonium acetate and trimethylamine, a combination of ammonium acetate and putrescine, torula yeast and Questlure, were evaluated in McPhail‐type traps. Two male lures targeting Ceratitis species: EGO Pherolure and trimedlure, were evaluated in Sensus bucket traps. Three male lures targeting Dacine fruit flies: methyl eugenol, cue lure and zingerone, were evaluated in Moroccan bucket traps. The three‐component Biolure was among the most effective food‐based attractant for females of Ceratitis capitata, C. rosa (R1 and R2), C. cosyra and Bactrocera dorsalis . EGO Pherolure attracted a wider range of Ceratitis species than trimedlure but was equally as effective as trimedlure for males of C. capitata and C. rosa (R1 and R2). Dacine flies were specific in their responses to male lures. Bactrocera dorsalis males responded mainly to methyl eugenol. Males of Dacus species responded to either cue lure or zingerone. Zingerone attracted two cucurbit‐infesting Dacus species: D. frontalis and D. durbanensis . For B. dorsalis, C. capitata and C. cosyra in commercial fruit production areas, patterns of female catches in traps containing food‐based attractants were different to patterns of male catches in male lure‐based traps. Implications of these trapping results are discussed.